2020
DOI: 10.1016/j.biochi.2020.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and modulation of brain lipids content of rainbow trout fed with 100% plant based diet rich in omega-3 long chain polyunsaturated fatty acids DHA and EPA

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Rainbow trout are the most widely utilized fish for assessing the acute toxicity of effluents. For AA and DHA, in rainbow trout, the fatal concentrations generating a 50% death rate in 96 hours (LC 50 /96 h) were 0.7-1.5 and 0.8-1.7 mL, respectively (Gregory & James, 2014;Wu et al, 2020), while in Daphnia Magna, the LC 50 /48 h values were 2.5-6.4 and 19.2 mg/L, respectively (Roy et al, 2020). Furthermore, allergic effects have been documented for AA and DHA.…”
Section: Discussionmentioning
confidence: 99%
“…Rainbow trout are the most widely utilized fish for assessing the acute toxicity of effluents. For AA and DHA, in rainbow trout, the fatal concentrations generating a 50% death rate in 96 hours (LC 50 /96 h) were 0.7-1.5 and 0.8-1.7 mL, respectively (Gregory & James, 2014;Wu et al, 2020), while in Daphnia Magna, the LC 50 /48 h values were 2.5-6.4 and 19.2 mg/L, respectively (Roy et al, 2020). Furthermore, allergic effects have been documented for AA and DHA.…”
Section: Discussionmentioning
confidence: 99%
“…Under voluntary FI, we reported that fish could distinguish between diets containing different levels of ω-3 LC-PUFA and exhibit a preference for diets containing high levels of EPA and DHA. Furthermore, we observed that a diet rich in ω-3 LC-PUFA accounted for a relatively high proportion of brain function [11] and brain lipid content [12] in RT juveniles. These recent studies have disclosed implications of ω-3 LC-PUFA on the modulation and regulation on the control of FI particularly the fatty acid (FA) sensing pathways even though molecular pathways remain to be elucidated.…”
Section: Introductionmentioning
confidence: 74%
“…Nutrient compositions of the diets were analyzed by drying the samples to constant weight at 105 °C for 24 h. Crude protein was determined by the Kjeldahl method after acid digestion and the concentration was estimated by multiplying the nitrogen content using the 6.25 factor as commonly used [32]. Crude lipids were quantified by the Soxhlet method using petroleum diethyl ether for the extraction as previously described [12]. Gross energy was determined with an adiabatic bomb calorimeter (IKA, Heitersheim Gribheimer, Germany).…”
Section: Proximate Compositionmentioning
confidence: 99%
“…As noted above, nutritional regulation of both fads2 and elovl2 but not elovl5 was observed, with increased expression of those genes in brain of fish fed the VO diets. These results indicate that tambaqui is, to some extent, able to guarantee the high DHA demand in brain when fed on diets containing suboptimal levels of this essential nutrient (Roy et al, 2020). Consistently, our study on the functional characterization of LC‐PUFA biosynthesizing enzymes in tambaqui demonstrated that both elovl2 and fads2 play key roles in the biosynthesis of DHA (Ferraz et al, 2019).…”
Section: Discussionmentioning
confidence: 91%